External Congenital Lacrimal Sac Fistula: А Case Report - Valcheva Kr. (Sciendo, 2018)
Congenital lacrimal fistula is a developmental abnormality. This is a case of a patient with an external congenital lacrimal sac fistula. Surgical treatment was used to correct the condition. Immediate postoperative results were seen. To present a case of a patient with an external congenital lacrimal sac fistula, in which surgical treatment was applied and immediate postoperative results with a good outcome were seen. A 3-year-old boy with an external congenital lacrimal sac fistula presented to our clinic. The skin orifice was observed on the left eye in a typical place – located in the inferomedial aspect of the medial canthal angle. The patient was treated in the at the Eye clinic, at university hospital “Dr. Georgi Stranski” – Pleven, Bulgaria. He underwent a surgical procedure – simple fistula excision (closed fistula excision). The surgical technique was a successful closed fistula excision. In the immediate postoperative period there were no complications such as infection, recurrence or worsening of the epiphora, poor cosmetic results, bleeding or damage to the lid structures or nose. The prognosis for patients with congenital lacrimal fistulas is quite good. Many are asymptomatic and those who have symptomatic epiphora or mucoid discharge can be successfully treated by surgery. Several surgical options exist – closed fistula excision, dacryocystorhinostomy (DCR) with fistula excision and fistula excision with nasolacrimal intubation. Symptomatic congenital lacrimal sac fistulas can be treated successfully with excision alone.